Analisis Pemikiran Linguistik Al-Jurjānī Dalam Pengembangan Ilmu Nahwu Wazifi - Salwah Suherman; Haniah Haniah; Amrah Kasim (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2026)
Classical Arabic linguistic studies have made a significant contribution to the development of contemporary linguistic theory, one of which is reflected in the thought of ʿAbd al-Qāhir al-Jurjānī. This study aims to analyze al-Jurjānī’s linguistic thought and its relevance to the development of functional nahwu (nahwu waẓīfī), which emphasizes function and meaning in language use. The focus of the study is directed toward the concept of an-naẓm, which positions syntactic structure as the primary determinant of meaning, as well as the relationship between grammatical elements and semantic context. This research employs a qualitative approach using a library research method, analyzing al-Jurjānī’s major works, such as Dalā’il al-Iʿjāz and Asrār al-Balāghah, along with other relevant supporting literature. The findings indicate that al-Jurjānī’s thought is conceptually aligned with the fundamental principles of functional nahwu, particularly in viewing grammatical rules as a means to understand meaning, function, and communicative purpose, rather than merely as formal regulations. Therefore, al-Jurjānī’s linguistic thought makes an important contribution to the development of a more contextual, functional, and applicative paradigm of nahwu in contemporary Arabic linguistic studies